Soil boron extraction methods and alder response to boron additions in Andisols of Costa Rica - Segura, Manuel (2010)
The effect of B to Andisols on tree height, diameter and volume of 5 Alnus acuminata plantations was studied. Plantation initial ages in years were: 0.5 at Hermanas Callejas (HC), 1 at Lechería Experimental (LE), 3 at Rosa Marta Cubero (RMC), 5 at Landelina (L) and 7 at Carter (C); at the end of the experiment plantations were 3 years older. B was supplied as Boronate and broadcasted at rates of 0, 2, 4, 6 and 8 kg.ha-1; the residual effect of fertilizer was determined 14 months after its application. The fertilizer added incre-mented B availability in the soils, as measured with pressurized hot water and Mehlich 3 methods. R2 values obtained were higher with correlations obtained by the Mehlich 3 procedure. The B applied did not cause increments of dasometric variables measured, except for a significant increase in volume of wood at Landelina (8 year old plantation). The lack of response in growth variables to B addition are attributed to the initial B availability in the soils (0.19-1.00 mg.kg-1), most values above the critical value of 0.5 mg.kg-1 mentioned for crops in Andisols, and the low requirement of B in alder. Foliar concentration of B showed a slight tendency to increase with growing amounts of B applied to the soil, while N foliar concentration did not show any tendency after B addition to the soil.